Increasing Marketing Performance through Development of Market Orientation and Entrepreneurship Orientation (A Study on the Participation of Micro, Small and Medium Enterprises (MSMEs) in Bengkulu Province) - Herry Novrianda; Aan Shar; Debby Arisandi (Budapest International Research and Critics University, 2022)
At this time, small, micro and medium enterprises (MSMEs) are required to continuously improve their performance. Moreover, if the market reach is not yet wide, business actors need to improve their marketing performance. The sampling method used a judgmental (purposive) technique with a sample size of 270 samples, namely owners/actors of micro, small and medium enterprises (MSMEs) in Bengkulu Province covering the districts of Kaur, Seluma, Lebong, Kepahiang, and Central Bengkulu whose businesses are in the trade and trade sector have been operating for at least the last 5 years. The research data were analyzed using the mean (mean) method and the frequency distribution table. The results of this study indicate that the MSME trade sector in Bengkulu Province has a good performance. This is because the MSMEs have been operating for 5 - 10 years (60.4%), even some of the MSMEs have been operating for 11-15 years (33.75) and > 15 years (5.9%). The types of MSME businesses in the trading sector in Bengkulu Province are food and beverage commodities from agricultural products (35.6%) and trade in agricultural products and live animals (29.3%). In addition, there are several other types of MSME businesses in the trading sector, such as retail trade in textiles and apparel (10%), personal goods (10%), household goods and second-hand goods (5.6%), and consumer goods. -craft items (5.6%). On average, the MSME sector actors also have the last education of SMA and Strata One (S1). Market orientation and entrepreneurial orientation support each other to improve the marketing performance of MSMEs in the trade sector in Bengkulu Province. The marketing performance of MSMEs in Bengkulu Province can be improved through the development of a market orientation that focuses on customer orientation activities but is also supported by competitor orientation and maintaining coordination between functions. In addition to improving the marketing performance of MSMEs through entrepreneurial orientation, MSMEs focus on innovation activities, being proactive and daring to take risks.